Nilai-Nilai Pendidikan Islam pada Pelaksanaan Piala Dunia FIFA 2022 Qatar - Sinulingga, Neng Nurcahyati; Sinulingga, Resti Oktriani (Institut Agama Islam Negeri Kediri, 2023)
Abstract: This study aims to analyze Islamic education values at the 2022 FIFA event Qatar. The Commercial image that has been attached, directly broken by the existence of Islamic Educational values embedded in every moment. Through a descriptive qualitative approach and supported by various related references source, this study shows that there are three values of Islamic Education in the implementation of the 2022 FIFA World Cup Qatar. The first is the moral education value, contained in the practice of prohibiting the sale of Beer and actions with LGBTQ nuances, the second is aqidah education value, contained in the practice of carrying out the opening ceremony of the holy verses of the al-Quran at the 2022 FIFA World Cup, as well as the installation of hadith murals along the streets of Doha in Qatar, and the third is social education value, contained in the practice of facilitating Barcode introduction of Islam in various hotels in Qatar. These values indirectly contribute in giving positive vibes and are able to create special effect that Islam is ‘rahmatan lil alamin’ for visitors, both spectators and supporters of the FIFA World Cup 2022 Qatar. Abstrak: Penelitian ini bertujuan untuk menganalisis nilai-nilai pendidikan Islam pada ajang Piala Dunia FIFA 2022 Qatar. Label komersial yang selama ini melekat seketika terpatahkan dengan adanya nilai-nilai pendidikan Islam yang disisipkan dalam setiap kegiatan yang ada. Melalui pendekatan kualitatif deskriptif dan didukung oleh berbagai sumber referensi yang yang terkait, penelitian ini menunjukkan bahwa ada tiga nilai pendidikan Islam yang ada dalam pelaksanaan ajang Piala Dunia FIFA 2022 Qatar. Pertama adalah nilai pendidikan akhlak, terdapat dalam praktik pelarangan terhadap penjualan Bir dan tindakan bernuansa LGBTQ; kedua adalah nilai pendidikan Aqidah, terdapat dalam praktik pelaksanaan upacara pembukaan ayat suci al-Quran dalam ajang Piala Dunia FIFA 2022 serta pemasangan mural hadis di sepanjang jalan Doha di Qatar, serta ketiga adalah nilai pendidikan sosial, terdapat dalam pengenalan fasilitas Barcode pengenalan Islam di berbagai Hotel di Qatar. Nilai-nilai pendidikan Islam ini secara tidak langsung turut memberikan lingkungan yang positif secara maksimal serta mampu memunculkan citra Islam yang rahmatan lil ‘alamin bagi para pengunjung, dan suporter Piala Dunia FIFA 2022 Qatar.